(untitled) - Turansky, Carrie (Thorndike, Maine, 2023)
"Two women -- a century apart -- embark on a journey to healing, faith, forgiveness, and romance. In 2012, art historian Gwen Morris travels to Englands Lake District to appraise the paintings and antiques of an old family friend, hoping to prove herself to her prestigious grandfather. While at Longdale Manor, she meets David Bradford -- the owners handsome grandson -- who is desperate to save the crumbling estate by turning it into a luxury hotel. When Gwen stumbles upon a one-hundred-year -old journal and an intricately carved shepherds staff similar to one in a photo of her parents, shes left searching for answers. In 1912, after her fathers death, Charlotte Harper uncovers a painful family secret she can only confess to her journal. She and her family travel to the Lake District to stay on a sheep farm, hoping eventually to find a home with Charlottes grandfather at Longdale Manor, but old wounds and bitter regrets make it a difficult challenge. As Charlotte grows closer to shepherd Ian Storey and rebuilds her shattered faith, she must decide whether she will ever trust in love again."--
Keywords: Fiction; Family secrets; England; Fiction; Man-woman relationships; Manors; Fiction; Family relationships; Women; Fiction; Lake District (England); Fiction; Large print books; Christian fiction; Romance fiction; Historical fiction